Characterization of imprinted albumin by molecular modelling and spectroscopy - Ilicheva, Polina M.; Reshetnik, Ivan A.; Drozd, Daniil D.; Pidenko, Pavel S.; Burmistrova, Natalia А. (Известия Саратовского университета. Новая серия Серия: Физика, 2025)
Background and Objectives: Imprinted proteins are promising alternatives to natural recognition systems, such as biological receptors or antibodies. However, the knowledge available on the theoretical study of imprinted proteins as recognition systems is limited. In this study, bovine serum albumin (BSA) is imprinted in the presence of 4-hydroxycoumarin. Change in protein structure is studied by molecular modelling and spectroscopy. Materials and Methods: To evaluate the effect of pH on the structural properties of BSA during imprinting, fluorescence 2D and 3D spectroscopy and dynamic light scattering (DLS) combined with molecular dynamics and metadynamics simulations were carried out to monitor the conformational change of the protein matrix. Results: Analysis of molecular dynamics simulation has shown that the mechanism of BSA conformational state changes is associated with displacements of molecular domains relative to each other. Based on molecular dynamics data, the values of collective variables have been selected for mapping the free energy of the system. The distance and angle between the centers of mass of domains D1 and D3 have been specified as collective variables. Simulations using themetadynamics method have been performed for 100 ns. As a result, slices of the potential energy surface have been obtained. Analysis of the free energy surface shows that 3.05 nm and 1.53 radian correspond to the minimum energy (ΔG = –6.14 kJ·mol–1). BSA have been studied by fluorescence and DLS. DLS analysis has shown that BSA exists predominantly in monomeric form in solution. In acidic media (pH 3.0) the significant changes of fluorescence properties of BSA have been observed. The results of molecular modelling are consistent with the experimental results. Conclusion: An important practical result of this study is that the theoretical study of such molecular systems combined with fluorescence characterization during synthesis can be applied to control imprinting process and to create new imprinted proteins with a wide range of applications.